Influence of the estrus synchronization protocol and the size of the corpus luteum on the fertility rate in recipients implanted with embryos produced in vitro - Mariani, Ana Carolina Bernardi; Lopes, Fernando Brito; Souza, Juliano Franco; Dias, Francisca Elda Ferreira; Arrivabene, Mônica; Sousa, José Adalmir Torres; Viana, Gregório Elias Nunes; Cavalcante, Tânia Vasconcelos (Comunicata Scientiae, 2013)
Morphological evaluation of the corpus luteum before embryo transfer is a method commonlyused for the selection of the bovine receptients. The present study evaluated the relation betweenthe corpus luteum and the estrous synchronization protocol on pregnancy rates in recipientsimplanted with in vitro-produced bovine embryos (IVP). 260 crossbred females were selected andsynchronized using two different hormonal protocols: G1 (n=110), with sodium cloprostenol, andG2 (n=150), with norgestomet associated with estradiol benzoate, equine chorionic gonadotrophinand sodium cloprostenol. Corpus luteum (CL) were evaluated on the day of the transfer of theembryos, through rectal palpation, and classified into four types: CL-1 (small), CL-2 (medium), CL-3(large) and CL-4 (enclosed). All transfers were conducted transcervically, in the horn ipsilateral tothe ovary containing the corpus luteum. Pregnancy was confirmed, 30 days after the transfer, byultrasound. The total pregnancy rate was 35,77%, distributed as follows: 17,69% in the recepients withCL-1 (n=46), 30,77% in the recepients with CL-2 (n=80), 43,85% in those with CL-3 (n=114) and 7,69% inrecepients with CL-4 (n=20), resulting in 16 (34,78%), 29 (36,25%), 41 (35,96%) and 7 (35,00%) pregnantfemales, respectively. The results suggest that there is no correlation between corpus luteum sizeand synchronization protocol and the pregnancy rates of bovine recepients implanted with PIVembryos.